Phosphorylation of spore coat proteins by a family of atypical protein kinases - Nguyen, Kim B. (Proc Natl Acad Sci U S A, 2016)
The modification of proteins by phosphorylation occurs in all life forms and is catalyzed by a large superfamily of enzymes known as protein kinases. We recently discovered a family of secretory pathway kinases that phosphorylate extracellular proteins. One member, family with sequence similarity 20C (Fam20C), is the physiological Golgi casein kinase. While examining distantly related protein sequences, we observed low levels of identity between the spore coat protein H (CotH), and the Fam20C-related secretory pathway kinases. CotH is a component of the spore in many bacterial and eukaryotic species, and is required for efficient germination of spores in Bacillus subtilis; however, the mechanism by which CotH affects germination is unclear. Here, we show that CotH is a protein kinase. The crystal structure of CotH reveals an atypical protein kinase-like fold with a unique mode of ATP binding. Examination of the genes neighboring cotH in B. subtilis led us to identify two spore coat proteins, CotB and CotG, as CotH substrates. Furthermore, we show that CotH-dependent phosphorylation of CotB and CotG is required for the efficient germination of B. subtilis spores. Collectively, our results define a family of atypical protein kinases and reveal an unexpected role for protein phosphorylation in spore biology.